(untitled) (Research, Society and Development, 2023)
Exercises using materials for elastic resistance have reached a considerable place in the systematization of resistance training, however, depending on your situation, use more functional displacement patterns compatible with the weight machine. This review aimed to analyze resistance training methods with elastic bands in the elderly, thus being able to evaluate training progress. As a methodology, a systematic and exploratory bibliographic review was adopted. 65 related articles were found that were published from 203 to 2021, all selected from the PubMed and Google Scholar database, using the descriptors: Elderly, elastic band, resistance training. to select 9 articles to be analyzed in this study. Articles focused on resistance training with elastic bands that are used in the elderly were analyzed, which can promote different significant advantages in terms of improving the physical capabilities of the elderly. Therefore, this type of training can be easily adopted into the daily lives of the elderly, thus reaching the conclusion that the study shows that resistance band exercise is a viable alternative for developing a resistance training program in the elderly. Obtaining significant results in resistance training.